Positive electrode optimized for improving high-temperature life characteristics and secondary battery comprising same
By using a mixed positive electrode active material of large and small particles in the positive electrode of lithium secondary battery, adjusting its particle size and mixing ratio, combining appropriate porosity and electrode density, the problem of particle cracking of the positive electrode material during rolling is solved. , significantly improves the battery's high-temperature life characteristics and cycle stability.
Patent Information
- Application Number
- CN202411358832.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-12
- Filing Date
- 2020-10-20
- Publication Date
- 2024-12-27
AI Technical Summary
The existing lithium secondary battery positive electrode materials are prone to particle cracking during rolling, resulting in deterioration of life performance at high temperatures, especially in small particles, which affects the high temperature stability and cycle life of the battery.
Using a mixed positive electrode active material with large and small particles, by adjusting its average particle size and mixing ratio, a combination of secondary particles and single particles is formed, combining suitable porosity and electrode density, reducing particle cracking and improving the high temperature life of the battery characteristic.
Through the optimal mixing ratio of large and small particles and rolling conditions, the particle cracking of the positive electrode active material is significantly reduced, and the life performance and cycle stability of the secondary battery at high temperatures are improved.
Abstract
Description
[0001] This application is a divisional application. The international application number of the original application is PCT / KR2020 / 014316, the application number of the Chinese national phase is 202080082255.0, the application date is October 20, 2020, and the name of the invention is "Positive electrode optimized for improving high temperature life characteristics and secondary battery containing the same". Technical Field
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of Korean Patent Application No. 10-2019-0170943, filed on December 19, 2019, and Korean Patent Application No. 10-2020-0131094, filed on October 12, 2020, in the Korean Intellectual Property Office, which are each incorporated herein by reference in their entirety.
[0004] The present invention relates to a positive electrode optimized for improving high temperature life characteristics and a secondary battery including the same. Background Art
[0005] As a part of the increasing demand for the use of alternative or clean energy due to the rapid increase in the use of fossil fuels, a very actively researched field is the field of power generation and energy storage using electrochemistry.
[0006] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of their use tends to gradually expand.
[0007] Recently, with the development of technology and the increase in demand for mobile devices such as portable computers, portable phones and cameras, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries that exhibit high energy density and working potential, long cycle life and low self-discharge rate have been much studied and have been commercialized and widely used.
[0008] In addition, with the increasing concern about environmental issues, electric vehicles, hybrid electric vehicles, etc. have been frequently studied, and such vehicles can replace vehicles using fossil fuels, such as gasoline vehicles and diesel vehicles (which are one of the main causes of air pollution). Although nickel-hydrogen secondary batteries are mainly used as power sources for electric vehicles and hybrid electric vehicles, active research is also being carried out on the use of lithium secondary batteries with high energy density and discharge voltage, and some of them are in the commercialization stage.
[0009] At present, as the positive electrode material of lithium secondary battery, lithium-containing cobalt oxide (LiCoO2) is mainly used. In addition, lithium-containing manganese oxides, such as LiMnO2 with a layered crystal structure and LiMn2O4 with a spinel crystal structure, and lithium-containing nickel oxide (LiNiO2) are also considered.
[0010] Among the above-mentioned positive electrode active materials, LiCoO2 is frequently used due to its excellent life characteristics and excellent charge and discharge efficiency. However, due to the poor structural stability of LiCoO2 and the limited resources of cobalt used as a raw material, it has poor price competitiveness, so its large-scale use as a power source in fields such as electric vehicles is limited.
[0011] LiNiO2-based cathode active materials have relatively low prices and high discharge capacity battery characteristics, but there are problems in that rapid phase transitions in the crystal structure may occur along with volume changes that occur during charge / discharge cycles, and stability may drop sharply when exposed to air and moisture.
[0012] In addition, lithium manganese oxides such as LiMnO2 or LiMn2O4 have advantages in that they have excellent thermal stability and a relatively low price, but have problems such as small capacity, poor cycle characteristics, and poor high-temperature characteristics.
[0013] Therefore, ternary or quaternary lithium transition metal oxides containing three or more transition metals have been developed recently by replacing a portion of LiNiO2 with Co, Mn or Al, etc.
[0014] The ternary or quaternary lithium transition metal oxide is generally used by forming secondary particles from primary particles.
[0015] However, lithium transition metal oxides in the form of secondary particles are prone to particle cracking during electrode rolling, which increases the specific surface area of the active material, exacerbating the degradation of storage and life performance at high temperatures. Such particle cracking of such secondary particles is more obvious in small particles with an average particle size (D50) of about 5 μm.
[0016] Therefore, there is an urgent need to develop a positive electrode that can minimize particle cracking during rolling of a positive electrode including a lithium transition metal oxide as an active material, thereby improving lifespan characteristics at high temperatures. Summary of the invention
[0017] Technical issues
[0018] The present invention aims to optimize the composition, mixing conditions and rolling conditions of a positive electrode active material to minimize particle cracking of the positive electrode active material, thereby improving the life characteristics of a secondary battery containing the positive electrode active material at high temperatures.
[0019] Technical Solution
[0020] The terms or words used in this specification and claims should not be interpreted as being limited to common or dictionary terms, and the present invention should be interpreted with meanings and concepts consistent with the technical ideas of the present invention based on the principle that the inventor can appropriately define the concepts of the terms in order to appropriately describe the contents of his invention in the best manner.
[0021] A cathode active material according to one embodiment of the present invention, a method for preparing the same, and a secondary battery including the cathode active material will now be described.
[0022] According to one embodiment of the present invention, there is provided a positive electrode, wherein a positive electrode mixture containing a positive electrode active material is formed on a positive electrode current collector,
[0023] The positive electrode active material comprises lithium transition metal oxide powder represented by the following chemical formula 1:
[0024] Li a Ni x Co y M z O 2-w A w (1)
[0025] in
[0026] M is at least one selected from the group consisting of Mn, Ti, Mg, Al, Zr, Mn and Ni,
[0027] A is a halogen substituted for oxygen, and
[0028] 1.00≤a≤1.05, 0.1≤x≤0.8, 0.1≤y≤0.8, 0.01≤z≤0.4, 0≤w≤0.001,
[0029] The lithium transition metal oxide powder is composed of:
[0030] Large particles in which primary particles are aggregated to form secondary particles, and the average particle size (D50) of the secondary particles is 7 μm to 17 μm; and
[0031] Small particles, in which single particles are formed and the average particle size (D50) is 2 μm to 7 μm,
[0032] wherein the mixing ratio of the large particles to the small particles is 5:5 to 9:1 by weight, and
[0033] The porosity of the positive electrode mixture is 22% to 35%.
[0034] Specifically, the average particle size (D50) of the large particles may be 9 μm to 11 μm, and the average particle size (D50) of the small particles may be 4 μm to 6 μm.
[0035] In addition, specifically, a mixing ratio of the large particles to the small particles may be 6:4 to 8:2 by weight.
[0036] In addition, specifically, the porosity of the positive electrode mixture may be 24% to 30%.
[0037] Also, the electrode density of the positive electrode may be 3.0 g / cc to 3.6 g / cc. Specifically, the electrode density of the positive electrode may be 3.2 g / cc to 3.45 g / cc.
[0038] Meanwhile, in the lithium transition metal oxide powder of Chemical Formula 1 contained in the positive electrode active material, M is Mn b Al c , where 0≤b≤1, 0≤c≤1.
[0039] The positive electrode mixture may further include a binder and a conductive material, wherein the binder is present in an amount of 1 wt % to 5 wt % based on the total weight of the positive electrode mixture, and the conductive material is present in an amount of 0.5 wt % to 5 wt % based on the total weight of the positive electrode mixture.
[0040] According to another embodiment of the present invention, a secondary battery is provided, in the structure of which an electrode assembly is placed in a battery box in a state of being impregnated with an electrolyte, wherein the electrode assembly includes: the positive electrode, the negative electrode, and a separator placed between the positive electrode and the negative electrode.
[0041] Beneficial effects
[0042] The positive electrode of the present invention comprises a positive electrode active material obtained by forming a single particle with small particles of a lithium transition metal oxide powder, and the porosity of the positive electrode mixture is set within an optimal range according to the mixing ratio of large particles and small particles and the rolling conditions, thereby improving the high temperature life characteristics of a secondary battery comprising the positive electrode. DETAILED DESCRIPTION
[0043] Hereinafter, the positive electrode and the secondary battery of the present invention will be described in more detail.
[0044] According to one embodiment of the present invention, there is provided a positive electrode, wherein a positive electrode mixture containing a positive electrode active material is formed on a positive electrode current collector,
[0045] The positive electrode active material comprises lithium transition metal oxide powder represented by the following chemical formula 1:
[0046] Li a Ni x Co y M z O 2-w A w (1)
[0047] in
[0048] M is at least one selected from the group consisting of Mn, Ti, Mg, Al, Zr, Mn and Ni,
[0049] A is a halogen substituted for oxygen, and
[0050] 1.00≤a≤1.05, 0.1≤x≤0.8, 0.1≤y≤0.8, 0.01≤z≤0.4, 0≤w≤0.001,
[0051] The lithium transition metal oxide powder is composed of:
[0052] Large particles in which primary particles are aggregated to form secondary particles, and the average particle size (D50) of the secondary particles is 7 μm to 17 μm; and
[0053] Small particles, in which single particles are formed and the average particle size (D50) is 2 μm to 7 μm,
[0054] wherein the mixing ratio of the large particles to the small particles is 5:5 to 9:1 by weight, and
[0055] The porosity of the positive electrode mixture is 22% to 35%.
[0056] As described above, generally, the lithium transition metal oxide represented by Chemical Formula 1 as a positive electrode active material is used in a secondary particle state.
[0057] In addition, large particles having an average particle size (D50) of about 11 μm and small particles having an average particle size (D50) of about 5 μm are mixed, but there is a problem in that the lithium transition metal oxide powder in the form of secondary particles may crack during electrode rolling.
[0058] In particular, particle cracking mostly occurs in small particles, and some particle cracking occurs in large particles.
[0059] Therefore, the inventors have found that in order to solve the above problems, when small particles are formed as single particles in lithium transition metal oxide powder, particle cracking can be reduced. However, when large particles in the form of secondary particles are mixed with small particles in the form of single particles, compared to the conventional case where large particles and small particles in the form of secondary particles are mixed, the cracking of large particles in the form of secondary particles increases (depending on the mixing conditions and rolling conditions of large particles and small particles), so that the degree of life degradation may become greater. Therefore, the inventors have found the optimal mixing ratio of large particles and small particles, the porosity and the optimal electrode density depending on rolling, and the cracking of large particles in the form of secondary particles has not increased compared to the existing structure, and completed the present invention.
[0060] Therefore, in the cathode of the present invention, the lithium transition metal oxide powder of Chemical Formula 1 included as the cathode active material is composed of a mixture of large particles in the form of secondary particles and small particles in the form of single particles.
[0061] In general, the average particle size (D50) of most lithium transition metal oxides in single particle form is about 5 μm, and small particles in single particle form are easy to manufacture, but in order to manufacture large particles in single particle form, the heat treatment temperature and time are too high, so it is not easy to prepare. As the particle size of the single particle increases, the charge / discharge efficiency and C rate characteristics decrease rapidly. Therefore, it is preferred to use large particles in the form of secondary particles.
[0062] In the present invention, the secondary particle form refers to a state in which several tens to several hundreds of primary particles are aggregated, and the single particle form refers to a form in which primary particles exist alone or are aggregated in less than 10 particles.
[0063] At this time, the major axis diameter of the primary particles constituting the large particles in the secondary particle form may be, for example, 100 nm to 1000 nm, and the major axis diameter of the primary particles constituting the small particles in the single particle form may be 500 nm to 7000 nm.
[0064] As defined above, the average particle diameter (D50) of large particles in the form of secondary particles formed by aggregation of tens to hundreds of such primary particles may be 7 to 17 μm, specifically, 9 to 11 μm.
[0065] In addition, as defined above, the average particle size (D50) of the small particles in the form of single particles (in which the primary particles exist alone or aggregated in less than 10 particles) may be 2 μm to 7 μm, specifically 4 μm to 6 μm.
[0066] When the average particle size (D50) of the large particles and the average particle size (D50) of the small particles exceed the above range and the average particle size of the large particles is too large, the low efficiency and low C rate characteristics of the small particles in the form of single particles are aggravated, thereby showing a decrease in capacity and a decrease in output. When the average particle size of the large particles is too small, the electrode rollability is deteriorated, and the particle cracking of the large particles is aggravated during rolling due to the small particles in the form of single particles, which may cause high temperature life degradation. At the same time, when the average particle size of the small particles in the form of single particles is too small, it is difficult to prepare due to deterioration in processability, and when its average particle size is too large, the charge / discharge efficiency and C rate characteristics are deteriorated, which is not preferred.
[0067] Here, the average particle size (D50) refers to the diameter at the point where the cumulative distribution of particle volume according to the particle size is 50%. The average particle size (D50) can be measured by laser diffraction. Specifically, after the powder to be measured is dispersed in a dispersion medium, it is introduced into a commercially available laser diffraction particle size measuring device (such as Microtrac S3500), and the difference in the diffraction pattern according to the particle size is measured when the particles pass through the laser beam, thereby calculating the particle size distribution. D50 can be measured by calculating the particle size at the point where the cumulative distribution of particle volume according to the particle size in the measuring device is 50%.
[0068] Meanwhile, according to the present invention, when small particles in the form of single particles and large particles in the form of secondary particles are mixed as described above, cracking of the large particles in the form of secondary particles may increase depending on the mixing conditions and the porosity conditions after rolling and the electrode density. Therefore, it is very important to adjust the mixing ratio of the large particles and the small particles and the porosity after rolling.
[0069] First, large particles and small particles are mixed by separately preparing each of these particles. At this time, the mixing ratio that exhibits the effect of the present invention may be specifically 5:5 to 9:1, more specifically 6:4 to 8:2, and still more specifically 7:3.
[0070] When the content of small particles is too large and exceeds the above range, the small particles with stronger particle strength aggravate the particle cracking of large particles during electrode rolling, and the high temperature life may be deteriorated. When the content of small particles is too small, the filling rate of small particles is small and the electrode density is reduced, which is not preferred.
[0071] Next, in order to demonstrate the effects of the present invention, the porosity of the positive electrode mixture may be 22% to 35%, specifically 24% to 30%, and more specifically 25% to 28%, according to adjustment of rolling conditions.
[0072] Here, the porosity is calculated as follows using the ratio of the electrode density to the true density of the total solid components of the positive electrode mixture.
[0073] (True density - electrode density) / true density × 100
[0074] When the porosity is too small and exceeds the above range, it means that the rolling strength is high. Therefore, there is a problem of increased particle cracking of large particles in the form of secondary particles. When the porosity is too large, the rolling strength is low, but the electrode density is correspondingly reduced, which is not preferred from the perspective of energy density. There is a problem of reduced output due to the loss of conductive paths between particles.
[0075] Based on the optimization of the porosity depending on the mixing ratio of large particles and small particles and the rolling conditions, the electrode density within the most preferred range for exerting the effect of the present invention can be determined, and the electrode density within the preferred range of the positive electrode of the present invention can be 3.0 g / cc to 3.6 g / cc, specifically 3.3 g / cc to 3.45 g / cc.
[0076] Electrode density can be calculated as the weight per unit volume excluding the current collector.
[0077] When the electrode density is too small and exceeds the above range, the energy per unit volume decreases, which is not preferable. When the electrode density is too large, there is a problem that particle cracking of secondary particles increases and high temperature life characteristics deteriorate.
[0078] Meanwhile, the positive electrode active material may include a lithium transition metal oxide powder represented by Chemical Formula 1. Specifically, in Chemical Formula 1, M may be Mn b Al c , wherein 0≤b≤1, 0≤c≤1. In other words, the lithium transition metal oxide powder contained as the positive electrode active material specifically contains a transition metal in its composition, and may contain one or more selected from the group consisting of a Li-Ni-Co-Mn oxide containing Ni, Co and Mn, a Li-Ni-Co-Al oxide containing Ni, Co and Al, and a Li-Ni-Co-Mn-Al oxide containing Ni, Co, Mn and Al.
[0079] The lithium transition metal oxide powder represented by Chemical Formula 1 may independently contain a lithium transition metal oxide having a composition selected from the range of Chemical Formula 1, but may also be a mixture of lithium transition metal oxide powders having several compositions within the range of Chemical Formula 1.
[0080] In addition, the positive electrode active material may further include compounds known as conventional positive electrode active materials, such as LiNiO2, LiMnO2, LiMn2O4, LiCo 1-d Mn d O2、LiNi 1-d Mn d O2(0.2 <d<1)、Li(Nia Co b Mn c )O4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-e Ni e O4, LiMn 2-e Co e O4 (0 < e < 2), LiCoPO4 or LiFePO4. It goes without saying that a small amount of a single one or a mixture of two or more of them can be further included.
[0081] However, based on the total weight of the positive electrode active material, the content of the lithium transition metal oxide represented by Chemical Formula 1 can be at least 60% by weight or more.
[0082] In addition to the positive electrode active material, the positive electrode mixture further includes a binder and a conductive material, and optionally may further include a filler.
[0083] The conductive material is used to impart conductivity to the electrode, and the conductive material can be used without specific limitation in the battery to be constructed as long as it does not cause a chemical change and has electron conductivity. Specific examples include: carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal cracking carbon black, carbon fiber, single-walled carbon nanotube (SWCNT), multi-walled carbon nanotube (MWCNT); graphite such as natural graphite and artificial graphite; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. Any one or a mixture of two or more of them can be used. Based on the total weight of the positive electrode mixture, the content of the conductive material can be 0.1% by weight to 30% by weight, particularly 0.3% by weight to 10% by weight, and more particularly 0.5% by weight to 5% by weight.
[0084] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesion strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), polyvinylidene fluoride - hexafluoropropylene copolymer (PVDF - co - HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene - propylene - diene polymer (EPDM), sulfonated EPDM, styrene - butadiene rubber (SBR), fluororubber, or various copolymers thereof, and any one or a mixture of two or more of them can be used. Based on the total weight of the positive electrode mixture, the content of the binder can be 1% by weight to 30% by weight, particularly 1% by weight to 10% by weight, and more particularly 1% by weight to 5% by weight.
[0085] In addition, the filler is optionally used as a component to suppress the expansion of the positive electrode. The filler is not specifically limited as long as it is a fibrous material that does not cause chemical changes in the corresponding secondary battery. Examples of fillers include olefin polymers such as polyethylene and polypropylene; and fibrous materials such as glass fiber and carbon fiber. In this case, the addition amount of the filler can be 0.1 wt % to 3 wt % based on the total weight of the positive electrode mixture.
[0086] There is no specific limitation on the positive electrode current collector, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the thickness of the positive electrode current collector can be 3 μm to 500 μm, and may have small irregularities formed on the surface of the current collector to improve the adhesion of the positive electrode active material. For example, it can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0087] In addition, according to another embodiment of the present invention, there is provided a secondary battery, in which the electrode assembly is placed in a battery box in a state of being impregnated with an electrolyte solution, wherein the electrode assembly includes:
[0088] positive electrode;
[0089] negative electrode; and
[0090] A separator is disposed between the positive electrode and the negative electrode.
[0091] Specifically, the secondary battery may be a lithium secondary battery.
[0092] The negative electrode may also be manufactured in the form of applying a negative electrode mix including a negative electrode active material to a negative electrode current collector, and the negative electrode mix may further include the above-mentioned conductive material and a binder and an optional filler in addition to the negative electrode active material.
[0093] As the negative electrode active material, a compound capable of reversibly inserting and deinserting lithium can be used. Specific examples thereof may include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metal substances capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloy, Sn alloy, or Al alloy; metal oxides capable of doping and dedoping lithium, such as SiO x(0 < x < 2), SnO2, vanadium oxides, and lithium vanadium oxides; or composites containing the above metal substances and carbonaceous materials, such as Si-C composites or Sn-C composites, etc., and any one or a mixture of two or more of them can be used. Additionally, a thin film of metallic lithium can be used as the negative electrode active material. Furthermore, both low-crystalline carbon and high-crystalline carbon can be used as carbon materials. Typical examples of low-crystalline carbon can be soft carbon and hard carbon. Typical examples of high-crystalline carbon can be amorphous, plate-like, flaky, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbeads, mesophase pitch, and high-temperature calcined carbon, such as coke derived from petroleum or coal tar pitch.
[0094] There is no specific limitation on the negative electrode current collector as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum cadmium alloy, etc. can be used. Additionally, the thickness of the negative electrode current collector can generally be 3 μm to 500 μm, and like the positive electrode current collector, it can have minute irregularities formed on its surface to enhance the adhesion strength of the negative electrode active material. For example, it can be used in various forms, such as film, sheet, foil, net, porous body, foam, and non-woven fabric.
[0095] The separator separates the negative electrode and the positive electrode and provides a channel for lithium ion migration. Any separator can be used without specific limitation as long as it is commonly used as a separator in lithium secondary batteries. Specifically, a separator with excellent moisture retention ability for the electrolyte and low resistance to the migration of electrolyte ions is preferred. In particular, a porous polymer film, such as a porous polymer film made of polyolefin polymers (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer), or a laminated structure of two or more layers thereof can be used. Additionally, conventional porous non-woven fabrics, such as non-woven fabrics made of high-melting-point glass fibers or polyethylene terephthalate fibers, etc., can also be used. Additionally, to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material can be used, and optionally, a single-layer or multi-layer structure can be used.
[0096] Additionally, the electrolyte used in the present invention can include, but is not limited to, organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, or molten inorganic electrolytes, etc. that can be used to prepare lithium secondary batteries.
[0097] Specifically, the electrolyte can include an organic solvent and a lithium salt.
[0098] As the organic solvent, any solvent can be used without specific limitation, as long as it can act as a medium through which ions participating in the electrochemical reaction of the battery can migrate. Specifically, as the organic solvent, ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone can be used; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene or fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC); alcohol solvents such as ethanol and isopropanol; nitriles such as R-CN (wherein R is a linear, branched or cyclic C2 to C20 hydrocarbon group, and may include a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes. Among them, carbonate solvents are preferred, and a mixture of cyclic carbonates (e.g., ethylene carbonate, propylene carbonate, etc.) with high ionic conductivity and high dielectric constant that can improve battery charge / discharge performance and low viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) can be more preferably used. In this case, when the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, the electrolyte can exhibit excellent performance.
[0099] Lithium salts can be used without specific restrictions, as long as they are compounds that can provide lithium ions for lithium secondary batteries. Specifically, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI or LiB(C2O4)2, etc. can be used as lithium salts. It is preferred to use lithium salts in a concentration range of 0.1M to 2.0M. If the concentration of the lithium salt is within the above range, since the electrolyte has appropriate conductivity and viscosity, it can exhibit excellent electrolyte properties, and lithium ions can be effectively migrated.
[0100] In order to improve the life characteristics of the battery, suppress the reduction of the battery capacity and increase the discharge capacity of the battery, in addition to the above-mentioned electrolyte components, one or more additives may be added to the electrolyte solution, for example: halogenated alkylene carbonate compounds (e.g., difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glycol dimethyl ether, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N, N-substituted imidazolidinones, ethylene glycol dialkyl ethers, ammonium salts, pyrroles, 2-methoxyethanol or aluminum chloride. In this case, the content of the additive may be 0.1 wt % to 5 wt % based on the total weight of the electrolyte solution.
[0101] The secondary battery of the present invention as described above can be used as a power source for portable devices such as mobile phones, notebook computers, digital cameras, and devices in electric vehicles such as hybrid electric vehicles (HEVs).
[0102] Hereinafter, embodiments of the present invention will be described in detail so that those skilled in the art can easily implement them. The present invention can be modified in various ways and is not limited to the embodiments set forth herein.
[0103] <Preparation Example 1> (Large particles in the form of secondary particles)
[0104] In a 5L intermittent reactor set at 60°C, nickel sulfate, cobalt sulfate and manganese sulfate were mixed in water at a molar ratio of 70:10:20 to prepare a metal salt solution of 2M concentration. A container containing metal salts was connected to enter the reactor. A 4M NaOH solution and a 7% NH4OH aqueous solution were prepared and connected to each reactor. 3 liters of deionized water were added to a coprecipitation reactor (capacity of 5L), and nitrogen was introduced into the reactor at a rate of 2 liters / minute to remove dissolved oxygen in the water and to make the inside of the reactor a non-oxidizing atmosphere. Then, 100ml 4M NaOH was added, and then maintained at a stirring speed of 1200rpm at a temperature of 60°C to reach pH 12.0. Then, the metal salt solution was added at a rate of 180ml / hr, the NaOH aqueous solution was added at a rate of 180ml / hr, and the NH4OH aqueous solution was added at a rate of 10ml / hr, and the coprecipitation reaction was carried out for 10 hours to synthesize the nickel-cobalt-manganese composite hydroxide Ni 0.7 Co 0.1 Mn 0.2 (OH)2 (average particle size (D50): 11 μm).
[0105] The obtained nickel-cobalt-manganese-based composite metal hydroxide particles were mixed with lithium hydroxide as a lithium raw material at a molar ratio of 1:1.07, and then heat-treated at 860°C in air for 15 hours to obtain large-particle LiNi0.7 Co 0.1 Mn 0.2 O2 powder (average particle size (D50): 11 μm).
[0106] In SEM observation, the large-particle cathode powder is in the form of secondary particles obtained by agglomerating dozens or more primary particles, and its shape is spherical or elliptical.
[0107] <Preparation Example 2> (Small particles in the form of single particles)
[0108] The nickel-cobalt-manganese composite oxyhydroxide Ni was synthesized in the same manner as in Preparation Example 1. 0.7 Co 0.1 Mn 0.2 (OH)2 (average particle size (D50): 4.5 μm), except that the coprecipitation reaction time in Preparation Example 1 was reduced to 3 hours.
[0109] The obtained particles of nickel-cobalt-manganese-based composite metal hydroxide were mixed with lithium hydroxide as a lithium raw material at a molar ratio of 1:1, and then heat-treated at 950°C in air for 15 hours to obtain small particles of LiNi 0.7 Co 0.1 Mn 0.2 O2 powder (average particle size (D50): 5 μm).
[0110] In SEM observation, the small-particle positive electrode powder is in the form of primary particles existing alone or in the form of aggregation of less than 10 particles, and its shape is spherical or elliptical.
[0111] <Preparation Example 3> (Small particles in the form of secondary particles)
[0112] The nickel-cobalt-manganese composite oxyhydroxide Ni was synthesized in the same manner as in Preparation Example 1. 0.7 Co 0.1 Mn 0.2 (OH)2 (average particle size (D50): 4.5 μm), except that the coprecipitation reaction time in Preparation Example 1 was reduced to 3 hours.
[0113] The obtained nickel-cobalt-manganese-based composite metal hydroxide particles were mixed with lithium hydroxide as a lithium raw material at a molar ratio of 1:1.7, and then heat-treated at 840°C in air for 15 hours to obtain small particles of LiNi 0.7 Co 0.1 Mn 0.2 O2 powder (average particle size (D50): 4.5 μm).
[0114] In SEM observation, the small-particle cathode powder is in the form of secondary particles formed by aggregation of dozens or more such primary particles, and its shape is spherical or elliptical.
[0115] <Example 1>
[0116] The large-particle positive electrode powder prepared in Preparation Example 1 was mixed with the small-particle positive electrode powder prepared in Preparation Example 2 in a weight ratio of 7:3 and used as a positive electrode active material. PVdF was used as a binder, and carbon black was used as a conductive material. The positive electrode active material, the binder, and the conductive material were fully mixed in NMP at a weight ratio of 96:2:2 to make a slurry (viscosity: 5000mPa s), which was then coated on a 20μm thick Al current collector, dried at 130°C, and then rolled at a pressure of 1.7 tons / cm to make a 74.5μm thick positive electrode.
[0117] <Example 2>
[0118] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the large-particle positive electrode powder prepared in Preparation Example 1 and the small-particle positive electrode powder prepared in Preparation Example 2 were mixed in a weight ratio of 5:5 and used as the positive electrode active material.
[0119] <Example 3>
[0120] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the large-particle positive electrode powder prepared in Preparation Example 1 and the small-particle positive electrode powder prepared in Preparation Example 2 were mixed in a weight ratio of 8:2 and used as the positive electrode active material.
[0121] <Example 4>
[0122] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the rolling pressure was 2.1 tons / cm and the electrode thickness was 73.1 μm.
[0123] <Example 5>
[0124] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the rolling pressure was 1.1 tons / cm and the electrode thickness was 76.8 μm.
[0125] <Example 6>
[0126] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the rolling pressure was 0.7 tons / cm and the electrode thickness was 78.4 μm.
[0127] <Comparative Example 1>
[0128] A positive electrode was prepared in the same manner as in Example 1, except that the large-particle positive electrode powder prepared in Preparation Example 1 and the small-particle positive electrode powder prepared in Preparation Example 3 were mixed at a weight ratio of 7:3.
[0129] <Comparative Example 2>
[0130] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the large-particle positive electrode powder prepared in Preparation Example 1 and the small-particle positive electrode powder prepared in Preparation Example 2 were mixed in a weight ratio of 4:6 and used as the positive electrode active material.
[0131] <Comparative Example 3>
[0132] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the rolling pressure was 2.5 tons / cm and the electrode thickness was 71.8 μm.
[0133] <Comparative Example 4>
[0134] A positive electrode was prepared in the same manner as in Example 1, except that in Example 1, the rolling pressure was 0.2 ton / cm and the electrode thickness was 82.8 μm.
[0135] <Test Example 1>
[0136] In the positive electrodes prepared in Examples 1 to 6 and Comparative Examples 1 to 4, the porosity and electrode density of the positive electrode mixture were obtained as follows, and the results are shown in Table 1 below.
[0137] *Porosity was calculated as follows using the ratio of the electrode density to the true density of the total solid components of the positive electrode mixture.
[0138] (True density - electrode density) / true density × 100
[0139] *Electrode density is calculated as weight per unit volume excluding the current collector.
[0140] Table 1
[0141] Porosity (%) Electrode density (g / cc) Example 1 25 3.36 Example 2 25 3.36 Example 3 25 3.36 Example 4 23 3.45 Example 5 28 3.21 Example 6 30 3.15 Comparative Example 1 25 3.36 Comparative Example 2 25 3.36 Comparative Example 3 21 3.55 Comparative Example 4 36 2.86
[0142] <Test Example 2>
[0143] Half coin cells were prepared using the positive electrodes prepared in Examples 1 to 6 and Comparative Examples 1 to 4 and lithium metal as a negative electrode, and using an electrolyte solution containing 1M LiPF6 in a solvent of EC:DMC:DEC=1:2:1.
[0144] The prepared half coin cell was charged at 25°C at a constant current (CC) of 0.1C until it reached 4.25V, and then charged at a constant voltage (CV) of 4.25V, and the first charge was performed until the charging current reached 0.05mAh. After that, it was left for 20 minutes, and then discharged at a constant current of 0.1C until it reached 3.0V, and the discharge capacity at the first cycle was measured.
[0145] It was charged to 4.25V at 0.5C under constant current / constant voltage (CC / CV) conditions at 45°C, and charged until it reached 0.05mAh, and then discharged to 3.0V at 1C under constant current (CC) conditions, and this was set as 1 cycle, which was repeated up to 50 cycles. The value calculated by "(capacity after 50 cycles / capacity after 1 cycle)×100" is defined as the high temperature life retention rate (%), and the results are shown in Table 2 below.
[0146] Table 2
[0147] Capacity retention at 45°C (%) Example 1 93 Example 2 89 Example 3 92 Example 4 89 Example 5 94 Example 6 92 Comparative Example 1 88 Comparative Example 2 86 Comparative Example 3 85 Comparative Example 4 85
[0148] Referring to Table 2 and Table 1, it can be confirmed that when the positive electrode satisfying the conditions of the present invention is used, the particles are less cracked and thus the high temperature life characteristics are excellent.
Claims
1. A positive electrode, wherein A positive electrode mixture containing a positive electrode active material is formed on a positive electrode current collector. The positive electrode active material comprises lithium transition metal oxide powder represented by the following chemical formula 1: Li a Ni x Co y M z O 2-w A w (1) in M is at least one selected from the group consisting of Mn, Ti, Mg, Al, Zr and Ni, A is a halogen substituted for oxygen, and 1.00≤a≤1.05, 0.1≤x≤0.8, 0.1≤y≤0.8, 0.01≤z≤0.4, 0≤w≤0.001, Wherein, the lithium transition metal oxide powder is composed of the following: Large particles in which primary particles are aggregated to form secondary particles, and the average particle size D50 of the secondary particles is 7 μm to 17 μm; and Small particles, wherein a single particle is formed and the average particle size D50 is 2 μm to 6 μm, wherein the single particle refers to a primary particle existing alone or in the form of an aggregation of less than 10 particles; wherein the mixing ratio of the large particles to the small particles is 5:5 to 9:1 by weight, Wherein, the electrode density of the positive electrode is 3.21 g / cc to 3.45 g / cc; Here, the major axis diameter of the primary particles constituting the small particles in the form of single particles is 500 nm or more.
2. The positive electrode according to claim 1, wherein The large particles have an average particle size D50 of 9 μm to 11 μm.
3. The positive electrode according to claim 1, wherein The mixing ratio of the large particles to the small particles is 6:4 to 8:2 by weight.
4. The positive electrode according to claim 1, wherein M is Mn b Al c , where 0≤b≤1, 0≤c≤1.
5. The positive electrode according to claim 1, wherein The positive electrode mixture further includes a binder and a conductive material.
6. The positive electrode according to claim 5, wherein The binder may be included in an amount of 1 wt % to 5 wt % based on the total weight of the positive electrode mixture, and the conductive material may be included in an amount of 0.5 wt % to 5 wt % based on the total weight of the positive electrode mixture.
7. The positive electrode according to claim 1, wherein The major axis diameter of primary particles constituting the large particles in the form of secondary particles is 100 nm to 1000 nm.
8. A secondary battery, wherein an electrode assembly is placed in a battery case in a state of being impregnated with an electrolyte solution, wherein the electrode assembly comprises: The positive electrode according to claim 1; negative electrode; and A separator is disposed between the positive electrode and the negative electrode.
